The analysis of heart sounds based on linear and high order statistical methods - Ergen, B; Tatar, Y (Ieee, 2001)
This paper investigates the applicability of high order statistical autoregressive (AR-HOS) modeling method in analyzing biomedical signals. The autoregressive (AR) method using linear prediction and AR-HOS method using cumulants are applied on normal and pathological heart sound signals. It is found that the AR-HOS modeling a signal produce more accurate and higher resolution spectrum than AR modeling.
23rd Annual International Conference of the IEEE-Engineering-in-Medicine-and-Biology-Society -- OCT 25-28, 2001 -- ISTANBUL, TURKEY
Keywords: heart sound; signal modeling; high order statistic